2016
DOI: 10.1016/j.virusres.2015.10.027
|View full text |Cite
|
Sign up to set email alerts
|

La Piedad Michoacán Mexico Virus V protein antagonizes type I interferon response by binding STAT2 protein and preventing STATs nuclear translocation

Abstract: La Piedad Michoacán Mexico Virus (LPMV) is a member of the Rubulavirus genus within the Paramyxoviridae family. LPMV is the etiologic agent of “blue eye disease”, causing a significant disease burden in swine in Mexico with long-term implications for the agricultural industry. This virus mainly affects piglets and is characterized by meningoencephalitis and respiratory distress. It also affects adult pigs, causing reduced fertility and abortions in females, and orchitis and epididymitis in males. Viruses of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 75 publications
0
4
0
Order By: Relevance
“…These binding events inhibit phosphorylation and nuclear translocation of the STATs. In contrast, Rubulavirinae V proteins generally bind STAT1 or STAT2 via the C-terminal region alone ( Nishio et al 2002 , 2005 ; Pisanelli et al 2016 ), and this leads to the targeted degradation of STATs via the proteosomal pathway. This requires the recruitment of additional host proteins, such as DDB1 ( Lin et al 1998 ; Andrejeva et al 2002 ), that enable the polyubiquitination of STATs.…”
Section: Organization and Function Of The Proteins Resulting From Gene Editingmentioning
confidence: 99%
“…These binding events inhibit phosphorylation and nuclear translocation of the STATs. In contrast, Rubulavirinae V proteins generally bind STAT1 or STAT2 via the C-terminal region alone ( Nishio et al 2002 , 2005 ; Pisanelli et al 2016 ), and this leads to the targeted degradation of STATs via the proteosomal pathway. This requires the recruitment of additional host proteins, such as DDB1 ( Lin et al 1998 ; Andrejeva et al 2002 ), that enable the polyubiquitination of STATs.…”
Section: Organization and Function Of The Proteins Resulting From Gene Editingmentioning
confidence: 99%
“…www.nature.com/scientificreports/ Meanwhile, we have observed that the reduction in monocyte numbers in HIV patients may be associated with compromised immune function. Monocytes, as primary participants in the innate immune system, play a crucial role in antiviral infections through the IFN signaling pathway 54 . Monocytes serve as target cells for HIV-1 infection, and monocytes release inflammatory factors and differentiate upon HIV-1 infection, stimulated by the IFN signaling pathway 55 .…”
Section: Discussionmentioning
confidence: 99%
“…This contrasts with V proteins from other members of the Rubulavirinae subfamily. LPMV-V protein IFN evasion is similar to that of Henipavirus V protein with its selective binding with STAT2 protein, though not with STAT1, and with the inhibition of STATs phosphorylation and subsequent nuclear translocation ( Figure 3 ) [ 133 ].…”
Section: Role Of the P V And W Proteins In Ifn Antagonismmentioning
confidence: 99%